Investigation on the Passive Systems in Traditional Houses in Middle East Areas: Solutions and Effects of Natural Ventilation - Mousli, Kindah; Semprini, Giovanni (Advanced Aspects of Engineering Research Vol. 9, 2021)
The Middle East area has a specific culture and habits, enhanced by adaptation to the environment and local climate through the traditional building constructions where typical design, structures, and materials represent the basis for passive strategies. In these hot-dry regions, many traditional houses consist of compact design structures with an internal courtyard where the effects of thermal inertia and natural ventilation can be well exploited. This paper focuses on the analysis of passive techniques used in some houses located in Damascus old city, which are renowned for their distinctive adaptability. These traditional houses have a unique structure consisting of two levels: the first floor built with heavy mass stones, while the second has light mass (timber and mud). The presence of an internal courtyard on which several rooms of different sizes overlook, give rise to appreciable natural ventilation (single side or cross ventilation) through a proper opening of windows. Based on experimental data (air temperature, air velocity) acquired during a summer period in a traditional house, dynamic simulations for a different type of structures and openings are performed in order to investigate the influence of natural ventilation on reducing internal temperature and evaluate comfort conditions using ASHRAE standard. Results also suggest strategies to optimize passive techniques to reduce energy needs. The cross ventilation decreases the discomfort hours compared to the single-side ventilation, this depending on the effective characteristics of the building and to his thermal mass.